A Comparative Study of Children's Character Education Methods According to the Thinking of Zakiah Darajat and Thomas Lickona - Sanudin Ranam; Priyono; Muslim, Ibnu Fiqhan (Yayasan Sinergi Kawula Muda, 2023)
The aim of this study is to compare the views of Zakiah Daradjat and Thomas Lickona on the concepts of Islamic and Western character education. This research uses library research methods, which involve analysis of literature and previous research. The research results show that even though they come from different traditions, they both have similar goals, namely developing a generation that has good character and responsibility. Zakiah Daradjat emphasized the importance of human relationships with God and a spiritual approach to character formation. The focus involves understanding religion, developing sincerity, and awareness of responsibility towards God. On the other hand, Thomas Lickona emphasizes cultural and universal values in character education. He is vocal about defending universally recognized values, such as honesty, fairness, and respect, in everyday life. His thinking focuses on implementing character values in real action and creating individual awareness of their responsibilities towards themselves, others, and society.